MSP Guide - University, Wageningen (2015)
The MSP Guide Designing and facilitating effective multi-stakeholder p artnerships Get started Download now The MSP Guide(EN, FR, ES) Explore the rationale, principles and process of designing and facilitating e ffective MSPs Get it now The MSP Tool Guide Detailed descriptions of 6 0 tried-and-tested tools to facilitate multi-stakeholder partnerships Get it now Reflection Methods: Practical Guide Proven…